Effect of the consumption of brazzein and monellin, two recombinant sweet-tasting proteins, on rat gut microbiota - Veselovsky, Vladimir A.; Boldyreva, Daria I.; Olekhnovich, Evgenii I.; Klimina, Ksenia M.; Babenko, Vladislav V.; Zakharevich, Natalia V.; Larin, Andrey K.; Morozov, Maxim D.; Zoruk, Polina Y.; Sergiev, Petr V.; Dontsova, Olga A.; Maev, Igor V.; et al. (Frontiers in Nutrition, 2024)
Sweet-tasting proteins (SPs) are proteins of plant origin initially isolated from tropical fruits. They are thousands of times sweeter than sucrose and most artificial sweeteners. SPs are a class of proteins capable of causing a sweet taste sensation in humans when interacting with the T1R2/T1R3 receptor. SP thaumatin has already been introduced in the food industry in some countries. Other SPs, such as monellin and brazzein, are promising products. An important stage in researching SPs, in addition to confirming the absence of toxicity, mutagenicity, oncogenicity, and allergenic effects, is studying their influence on gut microbiota. In this paper we describe changes in the composition of rat gut microbiota after six months of consuming one of two recombinant SPs-brazzein or monellin. A full length 16S gene sequencing method was used for DNA library barcoding. The MaAsLin2 analysis results showed noticeable fluctuations in the relative abundances of Anaerocella delicata in brazzein-fed rat microbiota, and of Anaerutruncus rubiinfantis in monellin-fed rat microbiota, which, however, did not exceed the standard deviation. The sucrose-fed group was associated with an increase in the relative abundance of Faecalibaculum rodentium, which may contribute to obesity.Overall, prolonged consumption of the sweet proteins brazzein and monellin did not significantly change rat microbiota and did not result in the appearance of opportunistic microbiota. This provides additional evidence for the safety of these potential sweeteners.